PENGARUH BULLYING TERHADAP KESEHATAN MENTAL SISWA - Ningtias Putri Ayu Amalia; Titik haryati (LPPM Institut Pendidikan Nusantara Global, 2023)
This research was conducted with the aim of examining the Effects of Bullying on the Mental Health of SDS Budi Murni 1 Cipayung Students. The population of this study were fifth grade students at SDS Budi Murni 1 Cipayung, with a total of 30 students. The research sample was taken using the saturated sample technique and using a Likert scale as a data collection tool. The results showed that there was no significant effect between bullying and students' mental health. This can be seen from the results of statistical calculations, where the Fcount value is 792 while the Ftable is 4.20. The results of the simultaneous test show that the Fcount value is greater than Ftable 7.92 > 4.20 with a significance value of 0.381 > 0.05, which means that Hₐ is accepted. So it can be interpreted that there is no effect of bullying on mental health.